Albumin–to–Alkaline Phosphatase Ratio: Does It Predict Survival in Grade 1 and Grade 2 Neuroendocrine Tumors?. Issue 1 (January 2021) - Acikgoz, Yusuf; Bal, Oznur; Dogan, Mutlu
Abstract : Objectives: Neuroendocrine tumors (NETs) are very heterogeneous tumors. This study aimed to evaluate prognostic value of an albumin–to–alkaline phosphatase (ALP) ratio (AAPR) in well-differentiated NETs. Methods: A total of 110 patients were included in this study. Albumin–to–alkaline phosphatase ratio was calculated by dividing albumin concentration (g/dL) to ALP level (U/L). Cutoff value for AAPR was determined by receiver operating characteristic analysis. Survival analysis was performed by Kaplan-Meier method with the log-rank test. A P value of less than 0.05 was considered statistically significant. Results: The optimum cutoff value for AAPR was 0.028. Patients were divided into 2 groups as patients with AAPR of 0.028 or less (n = 22, 20%) and with AAPR of greater than 0.028 (n = 88, 80%). Patients with AAPR of greater than 0.028 had statistically longer overall survival compared with patients with 0.028 or less (not reached vs 96.8 months, P = 0.001). In addition, AAPR has been shown to be an independent prognostic factor for overall survival in multivariate analysis (hazard ratio, 3.99; 95% confidence interval, 1.26–12.61, P = 0.018). Conclusions: Patients with higher AAPR had more favorable prognosis compared with patients with lower AAPR. We demonstrated that AAPR can be of prognostic value in well-differentiated NETs.